MEMBINGKAI KONSEP PARIWISATA YANG BERKELANJUTAN MELALUI COMMUNITY-BASED TOURISM : SEBUAH REVIEW LITERATUR - Febriandhika, Ikke; Kurniawan, Teguh (Department of Public Administration, Universitas Negeri Surabaya, 2019)
Tourism has a positive impact, especially in economic aspects. The tourism activities involve interaction between the host community and tourist. One of the concepts in sustainable tourism development is Community-Based Tourism. This concept requires contribution and active participation of the local community in tourism development. The purpose of this study is to explain how the concept of sustainable tourism through Community-Based Tourism approach. This study used a qualitative method with a literature study. Finding of this study is the concept of Community-Based Tourism is used as tourism development design that focuses on the community with emphasizing the local potential and encouraging the community capacity development. The important aspects in the successful sustainable tourism development through Community-Based Tourism can be seen from various fields, like social-political, economic, environmental and cultural. In the social-political related to community involvement in decision-making, planning, and development. In the economic aspect aims to improve community welfare. While the environmental and cultural aspect associated with the protection of natural and cultural resources. ?????